Renegotiating Identities: Experiences of Loss and Recovery for Women With Bipolar Disorder - Fernandez, M.; Breen, Lauren; Simpson, T. (Sage Publications, 2014)
Along with major changes in mood, people living with bipolar disorder (BD) often experience recurrent hospital admissions, feelings of failure and hopelessness, social stigma, underemployment, and a loss of independence. In this study we explored the experiences of loss, coping, and recovery in a community sample of women living with BD. Ten women each participated in a semistructured interview. We used the constant comparative method to analyze the data. We identified three themes from the data: identity bound by the diagnostic label, multidimensional effects of the bipolar disorder identity, and strategies for renegotiating identity. For these women, recovery involved an ongoing process of balancing their sick self with their healthy self. The findings contribute to conceptualizations of loss, coping mechanisms for dealing with loss, and the relevance of loss in recovery for people living at the margins with BD.